Modeling and Analysis of Traffic Performance and Coverage of LTE Network with Automatic Cell Planning Method (Lowokwaru Subdistrict, Malang City) - Amien, Mohammad Miqdad Hasfhi; Aisah, Aisah; Waluyo, Waluyo (Jurnal Jaringan Telekomunikasi, 2023)
The growth of cellular network technology is very rapid, currently in generation 4 or Long Term Evolution (LTE), namely the development of the third generation. However, there is a problem in this case, namely that there are several cellular networks that are less than optimal considering the very high customer service needs from time to time. The purpose of this study was to improve the quality of performance of several cellular network parameters in the case study area in Lowokwaru District, Malang City. Based on the results that have been carried out by researchers, the results of the average RSRP value before optimization are -100.5 dBm after optimization to -85 dBm, for the average RSRP value before optimization is -10.67 dB after optimization to -6.78, for the SINR value before being optimized 7.6 after being optimized to 29.02 dB. The results value of traffic is 16 user points, the average value per user of downlink data before optimizing is 121 kbps to 128 kbps and the average value of uplink data throughput before optimization is 57.88 kbps 60, 93 kbps. The value of downlink voice throughput before being optimized was 7.16 kbps to 12.2 kbps and the average value of uplink voice throughput before being optimized was 6.43 kbps after being optimized to 12.8 kbps.